Fluxes of greenhouse gases at two different aquaculture ponds in the coastal zone of southeastern China. (August 2015) - Yang, Ping; He, Qinghua; Huang, Jiafang; Tong, Chuan
Abstract: Shallow water ponds are important contributors to greenhouse gas (GHG) fluxes into the atmosphere. Aquaculture ponds cover an extremely large area in China's entire coastal zone. Knowledge of greenhouse gas fluxes from aquaculture ponds is very limited, but measuring GHG fluxes from aquaculture ponds is fundamental for estimating their impact on global warming. This study investigated the magnitude of carbon dioxide (CO2 ), methane (CH4 ) and nitrous oxide (N2 O) fluxes from two coastal aquaculture ponds during 2011 and 2012 in the Shanyutan wetland of the Min River estuary, southeastern China, and determined the factors that may regulate GHG fluxes from the two ponds. The average fluxes of CO2, CH4 and N2 O were 20.78 mgCO2  m −2  h −1, 19.95 mgCH4  m −2  h −1 and 10.74 μgN2 O m −2  h −1, respectively, in the shrimp pond. The average fluxes of CO2, CH4 and N2 O were −60.46 mgCO2  m −2  h −1, 1.65 mgCH4  m −2  h −1 and 11.8 μgN2 O m −2  h −1, respectively, in the mixed shrimp and fish aquaculture pond during the study period. The fluxes of all three gases showed distinct temporal variations. The variations in the GHG fluxes were influenced by interactions with the thermal regime, pH, trophic status and chlorophyll- a content. Significant differences in the CO2 and N2 O fluxes between the shrimp pond and the mixed aquaculture pond were observed from September to November, whereas the CH4 fluxes from the two ponds were not significantly different. The difference in the CO2 flux likely was related to the effects of photosynthesis, biological respiration and the mineralization of organic matter, whereas the N2 O fluxes were controlled by the interactions between nitrogen substrate availability and pH. Water salinity, trophic status and dissolved oxygen concentration likely affected CH4 emission. Our results suggest that subtropical coastal aquaculture ponds are important contributors to regional CH4 and N2 O emissions into the atmosphere, and their contribution to global warming must be considered. Furthermore, we also suggest that aquaculture pond type should be considered when evaluating regional GHG budgets in coastal aquaculture ponds. Highlights: Aquaculture ponds in the coastal zone are sources of atmospheric CH4 and N2 O. Aquaculture pond types have a significant influence on GHG emissions. Aquaculture ponds have higher GHG emissions during the drained period.